Relationship and associated mechanisms between ambulatory blood pressure and clinic blood pressure with prevalent cardiovascular disease in diabetic hypertensive patients. Issue 16 (April 2017) - Hao, Zirui; Li, Guiping; Sun, Yue; Liu, Yan
Abstract : Abstract: The present study was to compare the association between ambulatory blood pressure (ABP) and clinic BP (CBP) with prevalent cardiovascular diseases (CVD); and the underlying mechanism would also be investigated concurrently. Diabetic hypertensive patients were enrolled and divided into 2 groups based on presence of CVD. Twenty-four hour-ABP monitoring was performed and between-group differences were evaluated and logistic regression analysis was conducted. A total of 568 diabetic hypertensive patients were enrolled, and the mean age was 60.8 years, male accounted for 67.8%. Mean durations of diabetes mellitus and hypertension were 6.1 ± 2.7 and 5.4 ± 3.3 years, respectively, and 20.6% had prevalent CVD. Compared to patients without CVD, patients with CVD had significantly higher body mass index (BMI), plasma aldosterone concentration (PAC), and serum sodium level. No significant between-group differences in CBP were observed. However, 24 hour-SBP, daytime-SBP and nighttime-SBP were all significantly higher in patients with CVD compared to those without CVD. Pearson correlation analysis showed that BMI was positively correlated with PAC and serum sodium level. Logistic regression analyses showed that the association between clinic SBP and DBP with CVD were progressively attenuated to nonsignificant. In contrast, both ambulatory SBP and DBP were independently associated with CVD. However, after being further adjusted for PAC, no significant association was observed between ambulatory SBP and CVD. In diabetic hypertensive patients, ABP is superior to CBP in relation to CVD. The association between ambulatory SBP and CVD may be dependent on aldosterone excess.